Cryptanalysis and design of chaos based image encryption schemes - Wong , Kuan Wai (2025)
Chaos theory has been widely applied in designing image encryptionschemes due to its deep connection with cryptographic properties, such assensitivity to initial conditions and unpredictability. However, many existing image encryption schemes have been shown to be insecure against cryptanalysis. Cryptanalysis is essential for uncovering potential vulnerabilities, as it evaluates the security of encryption schemes, identifies weaknesses, and guides the development of more secure frameworks. Our research reveals that the scheme proposed by Biswas et al. is vulnerable to known plaintext attacks, requiring a time complexity of 2264.28 encryptions. This is 2183.72 times faster than brute-force attacks. Similarly, a chosen plaintext attack on Ping et al.’s scheme reveals a reduced key space of 2216.51, down from the claimed 2356, and identifies inefficiencies in its Henon map-based sequential encryption method. These findings emphasize the need for a more comprehensive analysis of encryption schemes that utilize genetic algorithm and sequential encryption techniques.